Empaako 'Praise Names': An historical, sociolinguistic and pragmatic analysis - Isingoma, Bebwa (African Study Monographs, 2014)
This paper traces the origin of empaako “praise names” and explicates their sociolinguistic and pragmatic significance. The 14th (or 15th) century was marked by both political change in the Bunyoro-Kitara Kingdom of Uganda and the genesis of an important sociolinguistic phenomenon: the introduction of empaako, an idiosyncratic type of personal name in Runyoro-Rutooro (a language spoken in Uganda) used to show intimacy, endearment, and respect. The use of empaako emerged following the Biito (an aristocratic Luo clan) conquest of the Bunyoro-Kitara Kingdom. As most typical African personal names have explicit semantic content, the lexical meaninglessness of empaako in Runyoro-Rutooro indicates that they are borrowed from Luo (a Nilotic language), in which similar name forms with explicit semantic content exist. Although empaako are ubiquitous in everyday discourse and carry robust social import, they are only 12 and this raises the issue of their referential indeterminacy. In this paper, I examine this issue within the givenness hierarchy framework of Gundel, Hedberg, and Zacharski (1993).
Keywords: Runyoro-Rutooro; Empaako; Sociolinguistic import; Referential indeterminacy; Luo influence